2021
DOI: 10.3389/fendo.2021.620941
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A and Its Multi-Effects on Pancreas: Recent Advances and Prospects

Abstract: Vitamin A (VA), which is stored in several forms in most tissues, is required to maintain metabolite homeostasis and other processes, including the visual cycle, energy balance, epithelial cell integrity, and infection resistance. In recent years, VA molecules, also known as retinoids, have been extensively explored and used in the treatment of skin disorders and immune-related tumors. To date, several observational and interventional studies have explored the relationship between VA status and the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…The RA-signaling pathway plays critical roles in a wide range of developmental processes at multiple stages during embryogenesis [34]. In the pancreas, RA signaling is necessary for the onset of pancreagenesis; previous studies have demonstrated that inhibition of this RA signaling pathway leads to pancreas agenesis [35].…”
Section: Retinoid Actions In Pancreatic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The RA-signaling pathway plays critical roles in a wide range of developmental processes at multiple stages during embryogenesis [34]. In the pancreas, RA signaling is necessary for the onset of pancreagenesis; previous studies have demonstrated that inhibition of this RA signaling pathway leads to pancreas agenesis [35].…”
Section: Retinoid Actions In Pancreatic Developmentmentioning
confidence: 99%
“…The RA-signaling pathway plays critical roles in a wide range of developmental processes at multiple stages during embryogenesis [34]. In the pancreas, RA signaling is necessary for the onset of pancreagenesis; previous studies have demonstrated that inhibition of this RA signaling pathway leads to pancreas agenesis [35]. High levels of RA are crucial for initial pancreas specification, and RA is used in several protocols for stem cell differentiation and for pancreatic endoderm specification in culture.…”
Section: Retinoid Actions In Pancreatic Developmentmentioning
confidence: 99%
“…The plasma level of VA appears to be low in human patients with type 1 diabetes but elevated in those with T2DM [82,83]. VA is stored in pancreatic stellate cells [84]. RA treatment (0.5 mg/mouse intraperitoneally every other day) for 6 weeks is able to delay the onset of diabetes in NOD/Scid mice [85].…”
Section: The Effects Of Ra On Metabolismmentioning
confidence: 99%
“…Both mouse and rat studies have attributed the benefits of RA treatment to the improvement of pancreatic β cell functions [85,86]. More studies are needed to understand the roles of VA in the control of pancreatic functions, as discussed in [84]. In addition, the RA effects may be attributed to the regulation of glucose metabolism [87].…”
Section: The Effects Of Ra On Metabolismmentioning
confidence: 99%
“…Retinoic acid, as a product of retinol catabolism, can maintain the activity of vitamin A by activating retinoic acid receptor (RAR) and retinoid acid X receptor (RXR). Studies have confirmed that retinoid is highly associated with diabetes, islet function, and glucose and lipid metabolism by regulating the transcription of downstream target genes [ 12–14 ]. The RXRs are nuclear receptors that mediate the biological effects of retinoids by their involvement in retinoic acid-mediated genes activation.…”
Section: Introductionmentioning
confidence: 99%